In vitro release of diclofenac diethylamine from gels: evaluation of generic semisolid drug products in Brazil (Brazilian Journal of Pharmaceutical Sciences, 2013)
In order for the pharmacological action of a topical dermal drug product to occur, the drug must first be released from the vehicle to be available to penetrate the skin layers and reach the site of action. Drug release is mainly dependent on the characteristics of the formulation. Currently, to register a generic or a similar drug product in Brazil performance testing of topical drug products for local action is not required. In this context, this aim of this study was to evaluate the in vitro release of commercial diclofenac diethylamine gel products available on the Brazilian pharmaceutical market, using the vertical diffusion cell method. Factors which may influence the test, such as the type of membrane used, and the effect of the formulation characteristics on the diffusion rate were evaluated. Brazilian legislation currently allows generic drug products to contain excipients other than the reference drug, which may affect the drug release from the vehicle. Only one of the four generic drug products tested could be considered equivalent to the reference Cataflam Emulgel®. The cellulose acetate and polyethersulfone membranes tested were found to be interchangeable in the in vitro release studies carried out on this product.